2006
DOI: 10.1136/jech.2005.043109
|View full text |Cite
|
Sign up to set email alerts
|

Ecological association between suicide rates and indices of deprivation in the north west region of England: the importance of the size of the administrative unit

Abstract: A lack of effect was found once we move from ward to local authority level. This may happen because of the non-homogeneous nature of the local authorities in terms of their income and employment indices. In this sense, wards are more homogeneous. This means that in examining ecological risk factors, a balance was found between large areas (diluted effects but greater power) and small areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…In Hong Kong the STPUGs appeared to bear sufficient between-unit heterogeneity in their socioeconomic circumstances to display the associations of area characteristics with suicide, although its smaller number of units may limit the statistical power in the analysis. In contrast past research from other countries tend to show stronger associations at smaller spatial units, which may have greater within area homogeneity than larger units (Middleton et al, 2004;Rehkopf and Buka, 2006;Rezaeian et al, 2006). Future small-area analysis of suicide should not only consider the size of spatial units but also the number of observations, which would affect statistical power of the analysis.…”
Section: Socioeconomic Correlates Of Suicidementioning
confidence: 48%
See 1 more Smart Citation
“…In Hong Kong the STPUGs appeared to bear sufficient between-unit heterogeneity in their socioeconomic circumstances to display the associations of area characteristics with suicide, although its smaller number of units may limit the statistical power in the analysis. In contrast past research from other countries tend to show stronger associations at smaller spatial units, which may have greater within area homogeneity than larger units (Middleton et al, 2004;Rehkopf and Buka, 2006;Rezaeian et al, 2006). Future small-area analysis of suicide should not only consider the size of spatial units but also the number of observations, which would affect statistical power of the analysis.…”
Section: Socioeconomic Correlates Of Suicidementioning
confidence: 48%
“…the breakdown of social bonds between individuals and the society) may give rise to a state of social disintegration or fragmentation and increase population suicide rates (Durkheim, 1951). Research also indicates that the association between suicide rate and area characteristics may vary by sex and age group and size of spatial unit studied (Congdon, 1996b;Middleton et al, 2004;Rehkopf and Buka, 2006;Rezaeian et al, 2006). However, little is known about whether the differential associations by socioeconomic indicator, demographic group, and unit of spatial aggregation observed in Western countries could be similarly found in non-Western settings.…”
Section: Introductionmentioning
confidence: 88%
“…Sie ist ein unspezifi sches Ma ß , dessen latenter Gehalt bisher nicht pr ä zise umrissen ist. Sie ist ein guter Pr ä diktor f ü r fr ü he Mortalit ä t [20,21] und misst eine unspezifi sche Selbstwahrnehmung undiagnostizierter Erkrankungen, den langsamen R ü ckgang k ö rperlicher Reserven sowie Depression und erlebte Belastungen [22] . Subjektive Gesundheit wurde analog zu einer Vielzahl nationaler und internationaler Studien [23,24] mit einer einzigen Frage gemessen, die mittels einer F ü nfpunkteskala verbal mit " ausgezeichnet " , " sehr gut " , " gut " , " weniger gut " und " schlecht " bezeichnet war.…”
Section: Subjektive Gesundheitunclassified
“…It is a combination of physical and mental abilities of the groups or individuals to extract the inner powers and potentials of the organization for development (14). Measures of organizational behavior are attachment to work, perseverance and hard work, healthy relationships at work, community spirit, and collaboration (15). Rafiei et al, (2012) indicated that there is a significant relationship between spirituality in workplace of sport managers of Ghazvin province, Iran, and their organizational commitment.…”
Section: Introductionmentioning
confidence: 99%